Aktualne aspekty zjawiska kryminalizacji dopingu w sporcie - Szwarc, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Doping, which continues to accompany sport to an even greater extent than before, triggers reactions of which one is legal intervention. This includes an intervention of criminal law taking the form of an increased number of instances of criminalisation of different behaviours connected with doping. Different countries address the problem differently and the practice of fighting doping in sport differs. Criminal law regulations and other legal provisions can sometimes be found in penal codes or other legislative acts specifically adopted to regulate sport. Recently such regulations have increasingly become the subject of special acts on combating doping in sport. The scope of criminalisation of behaviours connected with doping as well as the severity with which they are punished also differ and no wonder that these practices are not free from controversies and doubts. The questions asked include whether there are reasons that constitute grounds for criminalisation of such behaviours, whether the values which are infringed as a result are legal values justifying intervention of criminal law, or whether such practice constitutes the respect that is desired for the principle of subsidiarity of criminal law and criminal liability as ultima ratio. Others challenge the subsidiarity principle of criminal law as the form of a similar treatment under this law of the same or similar behaviours taking place in various spheres of human activity, both in the sense of their criminalisation and the severity with which they are penalised. Hence the problem of reacting to doping with the use of instruments that are available under criminal law for combating organised crime.Pobierz artykuł P
Keywords: doping w sporcie; odpowiedzialność karna; zasada pomocniczości prawa karnego i odpowiedzialność karna jako ultima ratio; zasada spójności prawa karnego; zorganizowana działalność dopingowa w kontekście przestępczości zorganizowanej